LED lighting systems for smart buildings: a review. Issue 3 (23rd September 2020) - Chinchero, Héctor F.; Alonso, J. Marcos; Ortiz T, Hugo
Abstract : This study presents a review of smart light‐emitting diode (LED) lighting systems applied to smart buildings. The study is focused on drivers, protocols, technologies, communication networks and applications. An extended overview of the methodologies used for LED lighting control in smart buildings is addressed. The study also presents an integrated architecture able to achieve the necessary services and control methodologies for intelligent building energy management system for LED lightings systems in smart buildings.